Analysis Students’ Motivation in Learning English During Pandemic Covid-19 At Students of SMP Negeri 9 Raja Ampat Regency - Axelina, Mersi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2021)
The purpose of this study was to describe the level of students’ motivation in learning English during pandemic covid-19 at students of SMP Negeri 9 Raja Ampat Regency. Related to the research objectives used a qualitative research design with a descriptive approach. The research subject in this study were students of SMP Negeri 9 Raja Ampat Regency, totaling 44 students. In collecting data the researcher used a questionnaire with 24 statements and 15 interview questions. In analyzing the data, the researcher used Microsoft Excel 2007 program to calculate the data. The results showed that the level of students’ motivation in learning English during the pandemic could be said good category with a percentage value of 86.3%. After the researcher studied more deeply, the results showed that students' intrinsic motivation reached 65.9%, while students' extrinsic motivation reached 100%. Thus, it can be concluded that the level of students' motivation in learning English during pandemic covid-19 is influenced by students' extrinsic motivation.